Sartre and somatics for the pedagogy of movement in contemporary dance. Issue 1 (1st July 2020) - James, Maisie Beth; Stockman, Caroline
Drawing on somatic practice, psychology, philosophy and the dance experience, this article operationalizes Sartre's ideological response to movement pedagogy. The 'thisness' experience of embodiment during traditional dance styles negatively impacts on the realization of our body's somatic potential. However, Sartre's 'body-for-itself' mode can be stimulated with certain somatic practices, due to the concentration on the inner experience and sensations present in the body. In this sense, the body becomes a learning outcome in itself, through a deep and respectful connection with the dancer's inner being. Pedagogically, this combination of Sartre's theory with holistic techniques of the self, specifically the fundamental principles of Feldenkrais and dance literacy, can benefit the realization of individual potential during dance, and optimize positive embodiment. This article discusses initial materializations of the learning experiences of the dance student, informed by Sartre's thinking on embodiment, and a theoretical discussion of the pedagogical implications of Sartre's ideas for somatic pedagogy in contemporary dance.